Pengaruh Disiplin Kerja Dan Motivasi Terhadap Kinerja Karyawan Pada PT Altrak 1978 Bintaro - Anang Prananto; Kemas Vivi Andayani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the effect of work discipline and motivation on employee performance at PT Altrak 1978 Bintaro. The method used in this research is quantitative and the data is collected by questionnaires distributed via google form. The number of samples in this study were 72 respondents and the data analysis used was validity test, reliability test, normality test, multicolonierity test, heteroscedasticity test, multiple regression linear analysis, t test, f test and coefficient of determination analysis. The results of the study obtained that Work Discipline (X1) has a significant effect on Employee Performance (Y) with the regression equation Y = 5.789 + 0.852 X1. the results of the hypothesis test (t test) obtained a tcount value of 15.319> t table 1.666 and a significant 0.000 < 0.05. Thus Ho1 is rejected and Ha1 is accepted, meaning that there is an influence between Work Discipline and Employee Performance. Motivation (X2) has a significant effect on Employee Performance (Y) with the regression equation Y = 9.588 + 0.757 X2. The results of the hypothesis test (t test) obtained a tcount value of 12.415> t table 1.666 and a significance of 0.000 <0.05. So it can be concluded that Ho2 is rejected and Ha2 is accepted, meaning that there is an influence between Motivation on Employee Performance. Work Discipline (X1) and Motivation (X2) have a significant effect on Employee Performance (Y) with the regression equation Y = 4.982 + 0.620 X1 + 0.252 X2. The results of the hypothesis test (F test) obtained an Fhitung value of 129.124> Ftable 3.13 and a significant value of 0.000 <0.05. So it can be decided that Ho3 is rejected and Ha3 is accepted, meaning that there is an influence of Work Discipline and Motivation on Employee Performance of PT Altrak 1978 Bintaro